Constituent market orientation and ownership of virtual marketplaces - Love, Terence; Tellefsen, B. (Emerald Group Publishing, 2003)
This paper applies new empirically based knowledge in the area of Constituent Market Orientation to a seven-element taxonometric model of Virtual Organisation. The most effective distribution of resources and management attention in the development of combinations of real and virtual business solutions is identified for each of the seven alternative configurations. The paper concludes with a list of key concepts that offer owners and managers of virtual organisations analytically based heuristics founded on cross-sectoral empirical research.